2010
DOI: 10.1002/app.31810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of membrane thickness and heat treatment on the gas transport properties of membranes based on P84 polyimide

Abstract: P84 polyimide membranes with thicknesses ranging from 6 to 310 lm were successfully fabricated by spin coating. The glass transition temperature of the P84 powder was found to be 315 C using differential scanning calorimetry, whereas its decomposition temperature was 536 C using thermogravimetric analysis. Scanning electron microscopy was used to examine the morphology of the membranes. The permeability of single gas (He, N 2 , O 2 , and CO 2 ) and the ideal selectivity of gas pair (O 2 /N 2 , He/ CO 2 , CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Similar permeability values for polyimide P84 flat sheet membranes are also reported in the literature [ 60 , 61 ]. In the case of the single polyimide membranes, the low values of gas permeability and the fact that the temperature has positive influence are the two main characteristics of the membranes’ behavior.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar permeability values for polyimide P84 flat sheet membranes are also reported in the literature [ 60 , 61 ]. In the case of the single polyimide membranes, the low values of gas permeability and the fact that the temperature has positive influence are the two main characteristics of the membranes’ behavior.…”
Section: Resultssupporting
confidence: 88%
“…The pure polyimide membrane provides, at 25 • C, permeability values of 9.6, 9.9, 8.9, 0.6, 0.3, 0.1, and 0.2 Barrer for He, H 2 , CO 2 , O 2 , CO, N 2 , and CH 4 , respectively. Similar permeability values for polyimide P84 flat sheet membranes are also reported in the literature [60,61]. In the case of the single polyimide membranes, the low values of gas permeability and the fact that the temperature has positive influence are the two main characteristics of the membranes' behavior.…”
Section: Gas Permeability Performancesupporting
confidence: 85%
“…After this first drying procedure, the sample was annealed at 200 1C under vacuum for 24 h, in order to ensure the complete solvent removal. As often showed by many authors, the polymer thermal history can significantly affect the mass transport properties, as well as the performance of glassy polymer membranes [7,9,40]. However, it was observed that the pretreatment of Matrimid s films at 200 1C is able to produce membranes with gas transport properties stable for a period of at least 6 months, as no significant aging was detected from gas permeability measurements [41].…”
Section: Methodsmentioning
confidence: 81%
“…Several polyimide materials, based on different diamines and dianhydride moieties, have been characterized for gas separation applications, and some of them are currently employed in commercial membrane separation modules, used for oxygen enriched air production, biogas and natural gas upgrading, or hydrogen recovery from syngas [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The dense layer thickness gradually increased as the fillers loading amount improved. The increment in the dense layer was originated from the improvement of dope solution viscosity and thus, it improved permeability [51].…”
Section: Mixed-matrix Membrane Preparationmentioning
confidence: 99%